Produção e qualidade pós-colheita de batata-doce cultivada no semiárido nordestino - Freitas, Thaisy Gardênia Gurgel de (Universidade Federal Rural do Semi-Árido, 2018)
Pre-harvest practices can alter the production system and root quality of sweet potatoes, influencing the storage capacity of the potatoes. The objective of this study was to evaluate the production and post-harvest quality of sweet potato roots grown in the Northeastern Semi-arid region. Three experiments were carried out in the field in a randomized complete block design with four replications. The first experiment was carried out at two sites (Russas-CE and Upanema-RN), with three harvest ages (120, 145 and 180 days) and three root sizes (small, medium and large). The second experiment was carried out with five nitrogen doses (10, 40, 75, 110 and 150 kg ha-1) and five storage times (0, 15, 30, 45, 60), the third experiment was carried out with five doses (0, 50, 100, 150 and 200 kg ha-1) and five storage times (0, 15, 30, 45, 60), carried out in the city of Russas-CE and with the harvest at 165 days after planting. The roots were taken to the Food Technology Laboratory of UFERSA, where they were sanitized, characterized and stored in a cold room. The following analyzes were performed: Root yield, number of roots per plant, root mean mass, firmness, soluble solids, pH, titratable acidity, ratio, total soluble sugars, reducing sugars, starch and mass loss in the experiments in which storage was evaluated. Data were submitted to analysis of variance, being the quantitative factor (Time), analyzed by regression, using the SISVAR program. The roots of sweet potato presented higher yield and superior quality characteristics when harvested in Upanema-RN at 180 days. The highest root yield was observed in roots grown at 150 kg ha-1 of nitrogen. The quality characteristics did not change significantly at the same dose. In the experiment where potassium doses were evaluated, a higher root yield was observed in the 150 kg ha-1 dose culture. During storage, it was verified that at 60 days of storage the roots were of the desired quality for commercialization
Keywords: Adubação; Armazenamento; Idades de colheita; Ipomoea batatas L; Fertilization; Storage; Harvest ages; Ipomoea batatas L; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA